2007
DOI: 10.1136/adc.2006.100065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alteplase and heparin in maintaining the patency of paediatric central venous haemodialysis lines: a randomised controlled trial

Abstract: Alteplase is significantly more effective than heparin in preventing clot formation in central haemodialysis lines. This reduces morbidity and improves preservation of central venous access. It is more expensive, though relatively economic if packaged into syringes and stored frozen until needed, but reduces the costs of unblocking or replacing clotted lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…A prospective study in children in the UK compared heparin 5000 unit/ml to alteplase 1 mg/ml and showed a significant reduction in CVC clot formation with alteplase as the standard lock solution [32]. One unit in our survey had conducted an internal audit of rt-PA, which also showed a significant reduction in catheter malfunction [33].…”
Section: Discussionmentioning
confidence: 98%
“…A prospective study in children in the UK compared heparin 5000 unit/ml to alteplase 1 mg/ml and showed a significant reduction in CVC clot formation with alteplase as the standard lock solution [32]. One unit in our survey had conducted an internal audit of rt-PA, which also showed a significant reduction in catheter malfunction [33].…”
Section: Discussionmentioning
confidence: 98%
“…525 In the hemodialysis setting, alteplase 1 mg/mL was shown to be more effective than heparin 5,000 units/mL in reducing intraluminal clot between hemodialysis sessions. 526 A multicenter study of 577 pediatric cancer patients with CVADs reported that urokinase administration every 2 weeks reduced both CVAD occlusion rates and catheterrelated infections compared with heparin administration. 527 Most other studies that have reported the use of local thrombolytic agents reported therapy for CVAD blockage and, hence, restoration of patency.…”
Section: For Children With Fi Rst Vte Secondary To Structural Venous mentioning
confidence: 99%
“…Recently, Gittins et al [22] stated that alteplase is significantly more effective than heparin in preventing clot formation in central haemodialysis lines, what reduces morbidity, and improves preservation of central venous access.…”
Section: Discussionmentioning
confidence: 98%